Tid til IKKE at tale om forskel - Jenkins, Richard (Religionsvidenskabeligt Tidsskrift, 2002)
This paper outlines the currently-dominant ‘difference paradigm’ in the study of social identity, and argues that, for three reasons, it is time to move on. First, to concentrate on difference makes it impossible to understand what identity is and how it works. Second, to concentrate on difference is to fly in the face of the observable realities of everyday human life. Third, to concentrate on difference makes it impossible to deal with the core questions of social theory, or even, perhaps, to engage in social theory at all. It is proposed that a model of identification as simultaneously a matter of similarity and difference is required if these criticisms are to be met.